Synthesis of ethanol nanoparticle preparations of white oyster ‎mushroom (pleurotus ostreatus) extract using chitosan and the ionic ‎gelation method - Rahimah, Santun Bhekti; Mufllihah, Heni; Priani, Sani Ega (International Journal of Basic and Applied Sciences, 2025)
Indonesia is a country rich in natural resources, many of which have the potential to be used as ‎traditional medicinal ingredients—one example is the White Oyster Mushroom (Pleurotus ‎ostreatus). The White Oyster Mushroom is known for its high nutritional value, popularity among ‎the public, and ease of cultivation. It contains various active compounds with potential antioxidant ‎and anti-inflammatory properties, including vitamin C, ergothioneine, flavonoids, alkaloids, ‎tannins, saponins, and other phenolic compounds. Since ancient times, the use of mushrooms as ‎medicine in the community has been widely reported, and more research is being conducted to see ‎their potential to become standardized herbal medicine or phytopharmacology. The study aims to ‎describe the synthesis of ethanol-based nanoparticle preparations of White Oyster Mushroom ‎extract using chitosan as a stabilizing agent and the ionic gelation method. Based on the results of ‎the Particle Size Analyzer, Potential Zeta, and Transmission Electron Microscope (TEM) tests, ‎the oyster mushroom extract nano-emulsion showed that the preparation successfully qualified ‎for stable status as a nanoparticle with a size of less than 1000 nm and a potential zeta of more ‎than -30 mV‎.
Keywords: Chitosan; Ionic Gelation Method; Nanoparticles; Phenolic; White Oyster Mushroom Ethanol Extract